Towards Ethical Deployment of AI for Conservation Systems - Kaeser-Chen, Christine; Birch, Tanya; Chou, Katherine; Gadot, Tomer; Adam, Hartwig; Belongie, Serge; Robertson, Tim; Fegraus, Eric; Morris, Dan (Cornell, 2019)
The ability to collect, aggregate, and process “big data”, particularly with artificial intelligence (AI) tools, has the potential to facilitate breakthrough research in conservation. As institutions develop and deploy such systems at scale, it is critical that they be designed with ethics, fairness, and transparency best practices in mind. In this short paper, we outline potential ethical concerns around AI for conservation as a starting point for further work to advance.